Public Sphere without a Printing Press: Texts, Reading Networks, and Public Opinion in Venezuela during the Age of Revolutions. Issue 2 (August 2020) - Soriano, Cristina
Abstract: At the end of the eighteenth century, members of the colonial elite of the Captaincy General of Venezuela addressed a letter to the king of Spain in which they sought permission to have a printing press in the city of Caracas. In the letter, they argued that the establishment of such a press was fundamental for the economic and commercial development of the Captaincy. Months later, they learned that the permission for a printing press had been denied without further explanations. Venezuela became one of the last capital cities in colonial Spanish America to possess this technology. The lack of a printing press during this politically dynamic period moved by the Atlantic revolutions did not necessarily affect public access to reading, sharing of information, and political debate in Venezuela. Venezuela's unique geographical location, and its open and frequent connections with the Caribbean region during the Age of Revolutions allowed for the effective entrance and transit of people and written materials that spread revolutionary ideas and impressions, creating a dynamic and contested political environment. Here I argue that during the late-colonial period, semiliterate forms of knowledge transmission, partially promoted by Spanish reformism, mobilised a socially diverse public that openly debated the monarchical regime, the system of slavery, and the hierarchical socio-racial order of colonial society. The colonial public sphere in Venezuela was shaped, then, within a context of emerging socio-racial tensions and became a space of contestation and struggle, animated by the overlapping of contradictory political discourses. This study contributes to recent debates about the character, nature, and relevance of the public sphere in the colonial world. It explores the circulation of manuscripts and ephemeral written materials, the different modes of production and reception of texts that developed in the colonial context, and an analysis of the character of the urban spaces that facilitated the performativity of texts. It thus offers a new framework for understanding the emergence of a public sphere in Venezuela, a colonial peripheral province with no printing press.